Aplikasi Metode VaR Dan RAROC Atas Risiko Dan Pengembalian Hasil Pada Bank Syariah Mandiri - Astri Ridiawati; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to discuss the level of risk (loss) ofMudharabah Deposit investment and the rate of return (pengemblian result) fromBank Syariah Mandiri. This research uses 2 methods of Value at Risk (VaR) tomeasure risk level and Risk Adjusted Return on Capital (RAROC) method tomeasure risk returns that have been adjusted with risk. This research is expectedto provide information for investors about financial risks and investment capitalof sharia banking.The results of research using VaR and RAROC methods from financialstatements in Bank Syariah Mandiri for three years, 2014 - 2016 showed that thelevel of risk for 3 months is quite stable because the value of VaR (zero) isnegative and the VaR value (mean) is lower than the value Expected Returnsduring the Year 2014 - 2016. While the results of the RAROC method indicate thatthe level of profit that has been adjusted with the risk in Bank Syariah Mandiriconcluded that RAROC is positive, meaning the level of profit in Bank SyariahMandiri greater than the level of risk.Keywords: Risk, Return, Mudharabah Deposits, Value at Risk (VaR), RiskAdjusted Return on Capital (RAROC)